Rheological Characterization of Warm-Modified Asphalt Mastics Containing Electric Arc Furnace Steel Slags - M. Pasetto; A. Baliello; G. Giacomello; E. Pasquini (Advances in Materials Science and Engineering)
The environmental sustainability of road materials and technologies plays a key role in pavement engineering. In this sense, the use of Warm Mix Asphalt (WMA), that is, a modified asphalt concrete that can be produced and applied at lower temperature, is considered an effective solution leading to environmental and operational benefits. The environmental sustainability of WMA can be further enhanced with the inclusion of steel slag in partial substitution of natural aggregates. Nevertheless, such innovative material applied at lower temperatures containing warm additives and steel slag should be able to guarantee at least the same performance of traditional hot mix asphalts, thus assuring acceptable mechanical properties and durability. Therefore, the purpose of this study is to investigate the rheological behaviour of bituminous mastics obtained combining a warm-modified binder and a filler (material passing to 0.063 mm) coming from electric arc furnace steel slag. To evaluate the influence of both warm additive and steel slag, a plain binder and limestone filler were also used for comparison purposes. Complex modulus and permanent deformation resistance of bitumens and mastics were assessed using a dynamic shear rheometer. Experimental results showed that steel slag warm mastics assure enhanced performance demonstrating promising applicability.